Analysis of Service Quality and Customer Trust in Using J&T Goods Delivery Services Using the Servqual Method in the Parongpong and Lembang Areas - Arli Hope Sianturi; Jay Idoan Sihotang (Universitas Syiah Kuala, 2025)
Goods delivery services are currently developing very rapidly in Indonesia, one of which is JT. Behind the development of this delivery service, one must also pay attention to the quality of service, which increases customer confidence in using the service. The purpose of this research is to evaluate JNT services for customers, one of the leading delivery service companies in Indonesia. Servqual is the method chosen because this method uses a User Based-Approach which can measure service quality quantitatively in the form of a questionnaire and has service quality dimensions such as reliability, tangibles, responsiveness, assurance, and empathy. Data collection was carried out by directly observing those using JT services, then sampling questionnaires using the Slovin formula and a tolerance of 0.10% with a value of 100 respondents. It is known that the results of research from questionnaire data calculated using the Customer Statisfaction Index formula for JNT's service level reached a percentage of 79.75%. The final results of this presentation can help JNT to always pay attention to and improve more efficient services